Organization and administration of physical education : theory and practice - Greenberg, Jayne Debra; LoBianco, Judy L., 1969- (Reston, VA : SHAPE America, Society of Health and and Physical Educators, 2020)
'The purpose of this book is to assist the undergraduate student in understanding the roles and responsibilities of a physical education administrator through the theoretical and practical lens, as well as assist the physical education teacher or department chairperson in entering the role as a physical education administrator. These responsibilities are covered in five sections: leadership, organization, and planning; curriculum, instruction, assessment, and special events; facilities, equipment, and technology; communication, legal issues, and human resources; and financial management'--
The role of a physical education administrator as a leader / Jayne D. Greenberg and Judy L. LoBianco -- Management and operations / Jayne D. Greenberg -- Organizing and planning a quality physical education program / Jayne D. Greenberg and Judy L. LoBianco -- Curriculum development and evaluation / Nichole D. Calkins, Jayne D. Greenberg, and Lori S. Dunn -- Quality instruction / Nichole D. Calkins, Sheri J. Brock, Leah H. Robinson, Jayne D. Greenberg, and Kara K. Palmer -- Teacher evaluation / Miriam Kenyon, Kathleen Satterley, Jayne D. Greenberg, and Judy L. LoBianco -- Event planning and special programs / Jayne D. Greenberg -- Facilities, design criteria, and equipment / Christopher Hersl and Jayne D. Greenberg -- Technology in physical education / Collin Brooks, Richard Benvenuti, and Jayne D. Greenberg -- Communications, internal and external public relations, and advocacy / Carly Wright, Jayne D. Greenberg, and Judy L. LoBianco -- Legal issues in physical education / Jessica de Koninck, Shawn Ladda, Judy L. LoBianco, and Jayne D. Greenberg -- Human capital management / Lauren O'Mara and Jayne D. Greenberg -- Fiscal management / Jayne D. Greenberg -- Grant writing and outside funding / Alexandra M. Reyes and Jayne D. Greenberg.
Includes bibliographical references and index.
Keywords: Physical education and training -- United States -- Management; School sports -- United States -- Management